PENGARUH KOMPOSISI WARNA PADA RUANG KERJA TERHADAP STRES KERJA - Prasetya, Rahmawan Dwi (Institut Seni Indonesia Yogyakarta, 2007)
his study is the result of an investigation of the influence of physical work environmenttoward stress at work place, particularly the color composition used. The research subjectswere thirty students of ASMI (Secretary and Management Academy) who were divided intothree groups, namely the Harmonious group, The Disharmonious group, and the Controlledgroup. The Work Stress Scale was used in the measurement process. The measurement wasdone three times: before the experiment, in the middle of the experiment (first 2 hours), and afterthe experiment (last 2 hours). The result was analysed using the Analysis of Variance (ANAVA)A-Mix-B model of SPS-2000 software application. The result of this study illustrated that therewas a significant difference on work stress level impacted by color composition applied at workspace (F = 4.149, p = 0.026). The graphic of work stress average of the Harmonious groupshowed that Harmonious color composition did not affect the work stress significantly (t =0.520, p = 0.306). The dominantly white color composition that played a role as the Controlledgroup was in fact able to reduce the work stress. The graphic showed that the Controlled grouptended to decrease significantly with these values t = 1.825, p = 0.035, and the initial work stressaverage was (0.000) higher than the final one (- 22.800). The Disharmonious group showed thatthe color composition increased the work stress level (t = 3.177, p = 0.001). It was concluded thatHarmonious color composition at work space did not influence the work stress level, dominantlywhite color composition could reduce the work stress level, and inharmonious (Disharmonious)color composition application had chances to elevate the work stress level.keywords﻿﻿: color composition, work space, work stresKeywords